THE INFLUENCE OF BRAND ATTITUDE ON BEHAVIORAL INTENTION IN THE CONTEXT OF NATIONAL CARRIER’S SERVICE FAILURE - Owais B. AL-GHARAIBEH (Geo Journal of Tourism and Geosites, 2021)
Studies on the service failures involving a national carrier are still very limited. This present study strives to investigate the relationship between brand attitudes and behavioral intentions in the context of national carrier’s service failures as well as the moderating effect of causal attribution on the above main relationship. Data were collected from 419 airline passengers using the purposive sampling technique. Path analysis was used to analyze the data. The effect of brand attitude on behavioral intention is found to be positive significantly. The results also showed that out of the two dimensions of causal attribution, only stability moderates the relationship between brand attitudes on behavioral intention.